2009
DOI: 10.1097/mpa.0b013e318184f50c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pancreatic Cancer Cell Proliferation by Propranolol Occurs Through Apoptosis Induction

Abstract: The rate of apoptosis in PC-2 cells was higher after treatment with butoxamine than propranolol, suggesting that propranolol induces apoptosis in PC-2 cells via the beta2-adrenoceptors principally. Our data could be useful for developing beta-adrenoceptor antagonists for inducing apoptosis in pancreatic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 21 publications
3
48
0
1
Order By: Relevance
“…Zhang et al also reported that PRO was able to induce apoptosis in the PC-2 human pancreatic cancer cell line at concentrations of 100 μM [51], and reduce invasiveness in MIA PaCa-2 and BxPC-3 cell lines at the same concentration [52]. …”
Section: Pre-clinical Evidence In Cancer - In Vitro and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al also reported that PRO was able to induce apoptosis in the PC-2 human pancreatic cancer cell line at concentrations of 100 μM [51], and reduce invasiveness in MIA PaCa-2 and BxPC-3 cell lines at the same concentration [52]. …”
Section: Pre-clinical Evidence In Cancer - In Vitro and In Vivomentioning
confidence: 99%
“…Zhang et al showed that PRO limited the expansion of the PC-2 pancreatic cancer cell line and that this was due to an increased rate of apoptosis [51]. The pro-apoptotic action of PRO was found to be via blockade of the beta2-adrenergic receptor rather than beta1, as shown by the increased level of apoptosis induced by the selective beta2 antagonist butaxamine and the reduced level due to the beta1 blocker metoprolol.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…A number of in vitro studies have demonstrated the anti-proliferative, anti-migratory and cytotoxic properties of propranolol, particularly against lung adenocarcinoma [7, 8], colon carcinoma [9], breast carcinoma [10], nasopharyngeal carcinoma [11], ovarian cancer [12], pancreatic cancer [13-15] and gastric cancer cells [16]. Propranolol was also found to exert potent anti-angiogenic effects in vitro through direct mechanisms on vascular endothelial cells [17, 18] and by decreasing pro-angiogenic signaling in both stromal [19] and cancer cells [11, 20-23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that β-adrenergic antagonists may suppress cell proliferation and invasion and induce apoptosis in PanCa [14,22], and also β 2 -adrenergic agonist can stimulate the production of cAMP and activation of G-protein effectors Gs [23]. However, the mechanism of PanCa cell death induced by β 2 -adrenergic antagonist is not clear.…”
Section: Introductionmentioning
confidence: 99%